Betaine Treatment Attenuates Chronic Ethanol-Induced Hepatic Steatosis and Alterations to the Mitochondrial Respiratory Chain Proteome - Kusum K. Kharbanda; Sandra L. Todero; Adrienne L. King; Natalia A. Osna; Benita L. McVicker; Dean J. Tuma; James L. Wisecarver; Shannon M. Bailey (International Journal of Hepatology)
Introduction. Mitochondrial damage and disruption in oxidative phosphorylation contributes to the pathogenesis of alcoholic liver injury. Herein, we tested the hypothesis that the hepatoprotective actions of betaine against alcoholic liver injury occur at the level of the mitochondrial proteome. Methods. Male Wister rats were pair-fed control or ethanol-containing liquid diets supplemented with or without betaine (10 mg/mL) for 4-5 wks. Liver was examined for triglyceride accumulation, levels of methionine cycle metabolites, and alterations in mitochondrial proteins. Results. Chronic ethanol ingestion resulted in triglyceride accumulation which was attenuated in the ethanol plus betaine group. Blue native gel electrophoresis (BN-PAGE) revealed significant decreases in the content of the intact oxidative phosphorylation complexes in mitochondria from ethanol-fed animals. The alcohol-dependent loss in many of the low molecular weight oxidative phosphorylation proteins was prevented by betaine supplementation. This protection by betaine was associated with normalization of SAM : S-adenosylhomocysteine (SAH) ratios and the attenuation of the ethanol-induced increase in inducible nitric oxide synthase and nitric oxide generation in the liver. Discussion/Conclusion. In summary, betaine attenuates alcoholic steatosis and alterations to the oxidative phosphorylation system. Therefore, preservation of mitochondrial function may be another key molecular mechanism responsible for betaine hepatoprotection.